Intraindividual perception of open versus robot-assisted partial nephrectomy (PERCEPTION trial): an important complementing perspective to randomized controlled trials - Reimold, Philipp; Bourgeois, Luisa; Klefenz, Lia; Butea-Bocu, Marius Christian; Jacobi, Anna Lena; Flegar, Luka; Groeben, Christer; Huber, Johannes (Urologia internationalis, 2025)
Introduction: Randomized controlled trials comparing patients’ experience with open (OPN) vs. robot-assisted (RAPN) partial nephrectomy showed no clear advantages for RAPN. This contradicts our clinical impression, so we analyzed a cohort that underwent both approaches for bilateral renal tumors. The aim of our study was to compare their intraindividual perceptions of OPN and RAPN. Methods: Scar assessment and evaluation of patient-reported outcome measures were conducted. The questionnaires were retrospectively answered for postoperative day 5 after OPN and RAPN and, as a reference, for the date of presentation. Results: Results revealed longer hospitalization and ischemia times in patients with OPN, while ratings for physical condition and quality of life were better in the RAPN group. Stress, depression, and anxiety in cancer patients scored higher in the OPN group. Scar assessment revealed less patient-reported satisfaction after OPN. Patients favored RAPN when comparing both approaches directly and were more likely to recommend RAPN to a friend. Conclusion: This is the first study on the intraindividual perception of OPN vs. RAPN, revealing a comparative judgement clearly in favor of RAPN. Based on our findings, we designed the APPROACH trial to compare OPN and RAPN in a representative population under the conditions of routine care.
Gesehen am 21.10.2025